2018
DOI: 10.4314/jcas.v14i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Households’ choices of healthcare services in the north west region of Cameroon

Abstract: Efficient healthcare systems in developing economies are significant indicators of development. Health can either be optimised households' choices between preventive and curative healthcare services. In Cameroon like other developing countries, domestic healthcare service is either considered to be a normal or luxury good to households with competing alternative providers such as the public and private providers. To examine the healthcare preferences of households in the North West Region of Cameroon, a purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Unfortunately, the distribution is unequal as some areas have more and others less as compared to the population leading to difficulties to extend healthcare to all. The uneven distribution of heath units is not new in Cameroon as it is the cause of numerous diseases spread in some rural settings of the Country [12]. Using the example of the North West Region of Cameroon, the authors revealed how with the quest for proper healthcare, households are forced to make a choice on which health unit to use from the other.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the distribution is unequal as some areas have more and others less as compared to the population leading to difficulties to extend healthcare to all. The uneven distribution of heath units is not new in Cameroon as it is the cause of numerous diseases spread in some rural settings of the Country [12]. Using the example of the North West Region of Cameroon, the authors revealed how with the quest for proper healthcare, households are forced to make a choice on which health unit to use from the other.…”
Section: Discussionmentioning
confidence: 99%
“…Demand in this context is defined as the probability of choosing different types of malaria prevention practices in a malaria risk area, given the relevant characteristics of the individual and household. This model adopted and modified from the work of [40,13] as was summarised by [41] following the work of [42] formulates the utility that a person derives from choosing a particular malaria prevention option, that is,…”
Section: Analytical Methodologymentioning
confidence: 99%
“…Ethnonationalism took the form of native resistance to German colonial rule. In the Bamenda grassfields, the German expansion led by Dr. Eugene Zingtgraff was resisted by local ethnic groups (Mankon, Nso, Kom, Bafut, Fungom, Bum, Esimbi, Esu, Aghem, Fungong, and others), some of whom put up a fight to defend their chiefdoms against colonial encroachment (Gwanfogbe 2019).…”
Section: History Of Nationhood and Nationalism In Cameroonmentioning
confidence: 99%